Preparation method of low-shrinkage carbonized aerogel
By covering the resin on the surface of the carbon aerogel to form a composite material and carbonized under an inert gas, the problem of structural damage in the carbon aerogel during the carbonization process is solved, and the high porosity and strength are improved, and the thermal insulation and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202510488267.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-08-08
AI Technical Summary
Carbon aerogels are prone to shrink and collapse during carbonization, resulting in damage to the nanopore structure and affecting the insulation and mechanical properties of the material.
By uniformly coating the resin on the surface of the aerogel to form a composite material and carbonized under an inert gas, an amorphous carbon coated carbon aerogel is formed, and the resin layer provides external support to jointly inhibit the volume shrinkage of the aerogel.
Effectively reduce carbonization shrinkage, maintain high porosity and structural stability, improve compressive strength, improve thermal and mechanical properties, and simplify the preparation process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon aerogel preparation, and in particular relates to a method for preparing low-shrinkage carbonized aerogel. Background Art
[0002] Carbon aerogels are attractive for their low density, low thermal conductivity, high thermal conductivity in inert atmosphere (up to 2000 °C), and high infrared specific extinction coefficient (>1000 m 2 kg −1 ) makes it an ideal high-temperature thermal insulation material. Its excellent thermal insulation performance is closely related to its unique nanopore and skeleton structure. However, during the carbonization process, the nanopore structure is prone to shrinkage and collapse, resulting in irreversible microstructural damage. Specifically, shrinkage causes increased structural density, reduced toughness, and increased susceptibility to cracking. Reduced porosity leads to a decrease in specific surface area and reduced thermal insulation performance.
[0003] Currently, a relatively effective method is to enhance the toughness of the skeleton and inhibit its shrinkage by adding reinforcements (such as fibers, carbon nanotubes, and graphene). Fiber-based reinforcements are preferred due to their high aspect ratio and excellent strength. However, due to the shrinkage mismatch between the organic precursors and fibers during carbonization, the carbon aerogel can easily cause matrix shedding and cracking, affecting the mechanical and thermal insulation properties of the composite material. Furthermore, the organic precursor can shrink by as much as 30% during carbonization. Therefore, finding the right organic reinforcement that can synergize with the organic precursors during carbonization and effectively inhibit carbonization shrinkage is key to improving the performance of carbon aerogel materials. Summary of the Invention
[0004] To solve the above problems, the purpose of the present invention is to provide a method for preparing carbonized aerogel with low shrinkage, which can reduce the carbonization shrinkage of organic aerogel and simultaneously shrink synergistically with the organic aerogel during the carbonization process, inhibit the collapse of the matrix structure, maintain the stability of the material microstructure, and achieve optimization of thermal properties and improvement of mechanical properties.
[0005] The purpose of the present invention is achieved through the following solutions: A method for preparing low-shrinkage carbonized aerogel comprises the following steps: selecting a raw material combination consisting of aerogel and resin of the same composition; uniformly coating the surface of the aerogel with the resin in the raw material combination to obtain a composite material (with aerogel inside and resin coating outside); drying and curing the composite material; and carbonizing the composite material under an inert gas atmosphere to form an amorphous carbon-coated carbon aerogel.
[0006] The raw material combination is any one of a phenolic aerogel and a phenolic resin, a polyimide aerogel and a polyimide resin, a polyurethane aerogel and a polyurethane resin, a cellulose aerogel and a cellulose-based resin, and an epoxy aerogel and an epoxy resin. In each raw material combination, the phenolic aerogel and the phenolic resin are made from the same phenolic and aldehyde compounds, the polyimide aerogel and the polyimide resin are made from the same dianhydride and diamine, the polyurethane aerogel and the polyurethane resin are made from the same polyol and isocyanate, the cellulose aerogel and the cellulose-based resin are made from the same modified cellulose, and the epoxy aerogel and the epoxy resin are made from the same epoxy polymer.
[0007] Furthermore, the composite material is obtained by coating the resin on the surface of the aerogel using any one of sol-gel, brush coating, spray coating, spin coating, vapor deposition and solution impregnation.
[0008] Furthermore, the thickness of the outer resin of the composite material (resin coating the aerogel) on a single side is controlled to be ≤50 μm.
[0009] Furthermore, the inert gas used for carbonization under inert gas is argon or nitrogen.
[0010] Furthermore, the control parameters of the carbonization process under inert gas are: carbonization temperature of 600-1500° C., carbonization time of 1-5 h, and heating rate to the carbonization temperature of 2-10° C. / min.
[0011] Furthermore, the flow rate of the inert gas is 0.3-0.7 L / min.
[0012] Furthermore, the drying and curing of the composite material is carried out by gradient curing by increasing the temperature in a gradient manner. The steps of the gradient curing are: a. Pre-curing: After the curing temperature is raised to 50-80℃, keep it warm for 20-40 minutes, and the heating rate is ≤5℃ / min; b. Initial curing: After the curing temperature is raised to 80℃-120℃, keep warm for 30-60min at a heating rate of 3-5℃ / min; c. Deep curing: After the curing temperature rises to 120-160℃, the holding time is 60-120min, and the heating rate is 2-3℃ / min; d. Post-curing: Cool with the furnace or control the cooling rate to ≤5℃ / min.
[0013] The present invention is characterized by reducing carbonization shrinkage, and its mechanism mainly includes: (1) The coating forms a shell during the carbonization process, providing external support and inhibiting the collapse of the internal aerogel structure, thereby reducing the overall shrinkage.
[0014] (2) The coating layer can slow down the thermal decomposition rate of organic aerogels, reduce the rapid shrinkage of volatile components, and reduce the structural shrinkage caused by violent decomposition.
[0015] (3) The thermal expansion coefficient of the coating layer with the same composition is similar to that of the substrate, which reduces local shrinkage or cracking caused by uneven thermal stress.
[0016] (4) The coating layer and the substrate can form a more stable cross-linked network during co-carbonization, thereby improving the structural integrity of the carbonized product.
[0017] The present invention forms an external rigid support during the carbonization process of the resin coating, effectively restraining the volume shrinkage of the aerogel matrix. This not only reduces the shrinkage rate, avoids void collapse and structural damage, retains the high porosity (80%-95%) structure, and reduces the thermal conductivity of the material (0.02-0.05W / m•K), but also enhances the overall compressive strength, overcoming the brittleness of traditional aerogels. In addition, the present invention simplifies the preparation process and can customize material properties (such as density, porosity, mechanical strength, etc.) according to needs, thus having design flexibility. DETAILED DESCRIPTION
[0018] The following specific embodiments illustrate the embodiments of the present invention. Those skilled in the art can easily understand the other advantages and effects of the present invention from the contents disclosed in this specification. The described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention. Example 1
[0019] This embodiment provides a method for preparing a carbonized aerogel with low shrinkage, comprising the following steps: S1. Raw material selection: A raw material combination consisting of a phenolic resin and a phenolic aerogel of the same composition is selected for standby use, wherein the selected phenolic resin is a thermosetting RF resin (Resole type) and the selected phenolic aerogel is an RF aerogel.
[0020] S2. Coating resin: Using a surface spraying process, the thermosetting RF resin (Resole type) is diluted with ethanol, and then the thermosetting RF resin (Resole type) is evenly sprayed on the surface of the RF aerogel using a spray gun, thereby obtaining a composite material with RF aerogel inside and thermosetting RF resin (Resole type) coated on the outside. The thickness of the sprayed RF resin is controlled within 50μm.
[0021] S3. Drying and curing: The prepared composite material is placed in a drying oven for drying and curing. Drying and curing is performed by gradient curing of the composite material using a gradient temperature increase method. The steps of the gradient curing are: a. Pre-curing: Raise the curing temperature in the drying oven to 50°C and keep it warm for 40 minutes, with a heating rate of 3°C / min.
[0022] b. Preliminary curing: Raise the curing temperature in the drying oven (from 50°C) to 80°C, keep warm for 60 minutes, and increase the temperature at a rate of 4°C / min.
[0023] c. Deep curing: Then increase the curing temperature in the drying oven (from 80°C) to 120°C, keep warm for 100 minutes, and increase the temperature at a rate of 3°C / min.
[0024] d. Post-curing: Finally, the composite material is cooled to room temperature in the furnace.
[0025] S4. Inert atmosphere co-carbonization treatment: The composite material obtained in step d was placed in a graphite boat, placed in a carbonization furnace, and high-purity argon with a flow rate of 0.5 L / min was used as a protective gas. The temperature was raised from room temperature to 300°C at a rate of 5°C / min, and then from 300°C to 1050°C at a rate of 8°C / min, and kept warm for 3 hours. The temperature was then lowered to room temperature at a rate of 8°C / min, thereby obtaining an amorphous carbon-coated carbon aerogel composite material.
[0026] Preparation of control group 1: The RF aerogel was directly carbonized according to step S4 to obtain carbon aerogel.
[0027] The linear shrinkage of the carbon aerogel composite material coated with resin (Example 1) and uncoated with resin (Control Group 1) is shown in Table 1.
[0028] Table 1 Comparison of linear shrinkage of carbon aerogels coated with resin and without resin
[0029] It can be seen from Table 1 that, compared with the control group 1, after coating the sample in the manner described in Example 1, the inert atmosphere co-carbonization treatment in step S4 can significantly reduce the linear shrinkage of the carbon aerogel composite material produced after carbonization. Example 2
[0030] This embodiment provides a method for preparing a carbonized aerogel with low shrinkage, comprising the following steps: S1. Raw material selection: A raw material combination consisting of a polyimide resin and a polyimide aerogel of the same composition is selected for standby use, wherein the selected polyimide resin is a biphenyl-type polyimide resin (PMDA-ODA) and the polyimide aerogel is a biphenyl-type (PMDA-ODA).
[0031] S2. Coating Resin: Using a surface coating process, evenly apply biphenyl polyimide resin (PMDA-ODA) to the biphenyl polyimide aerogel surface with a soft-bristle brush. Coat all five sides first. Once cured, coat the bottom surface and cure. This creates a composite material with an internal RF aerogel and an external coating of thermosetting RF resin (Resole). Maintain a coating thickness of less than 50 μm.
[0032] S3. Drying and curing: First, coat the five sides as described in step S2. After curing is completed, coat the bottom surface. The two curing steps are both performed by gradient temperature increase to perform gradient curing on the composite material, and the two curing steps are the same. The steps of the gradient curing are: a. Pre-curing: Raise the curing temperature in the drying oven to 50°C and keep it warm for 40 minutes, with a heating rate of 3°C / min.
[0033] b. Preliminary curing: Raise the curing temperature in the drying oven (from 50°C) to 80°C, keep warm for 60 minutes, and increase the temperature at a rate of 4°C / min.
[0034] c. Deep curing: Then increase the curing temperature in the drying oven (from 80°C) to 120°C, keep warm for 100 minutes, and increase the temperature at a rate of 3°C / min.
[0035] d. Post-curing: Finally, the composite material is cooled to room temperature in the furnace.
[0036] S4. Inert atmosphere co-carbonization treatment: The composite material obtained in step d was placed in a graphite boat, which was placed in a carbonization furnace. High-purity argon with a flow rate of 0.5 L / min was used as a protective gas. The temperature was raised from room temperature to 300°C at a rate of 5°C / min, and then from 300°C to 800°C at a rate of 8°C / min. The mixture was kept warm for 2 hours, and then cooled to room temperature at a rate of 8°C / min to obtain an amorphous carbon-coated carbon aerogel composite material.
[0037] Preparation of control group 2: Biphenyl polyimide aerogel (PMDA-ODA) was directly carbonized according to step S4 to obtain carbon aerogel.
[0038] Preparation of control group 3: The scheme of control group 3 is consistent with that of embodiment 2, except that control group 3 does not adopt gradient heating curing in the coating and curing stage (step S3), but adopts room temperature constant temperature curing.
[0039] The linear shrinkage of the carbon aerogel composite materials of the comparative coated sample (Example 2), the uncoated sample (Control Group 2) and the non-gradient cured sample (Control Group 3) is shown in Table 2.
[0040] Table 2 Comparison of linear shrinkage of carbon aerogels coated with resin, uncoated with resin, and coated with resin without gradient curing
[0041] Table 2 shows that, compared with Control 2, coating the sample in the manner described in Example 2 followed by inert atmosphere co-carbonization in step S4 significantly reduced the linear shrinkage of the carbon aerogel composite material produced after carbonization. Compared with Control 3, coating the sample followed by gradient curing in Example 2 significantly reduced the linear shrinkage of the carbon aerogel composite material produced after carbonization. Example 3
[0042] This embodiment provides a method for preparing a carbonized aerogel with low shrinkage, comprising the following steps: S1. Raw material selection: A raw material combination consisting of a phenolic resin and a phenolic aerogel of the same composition is selected for standby use, wherein the phenolic resin is a thermoplastic PF resin (Novolac type) and the phenolic aerogel is a PF aerogel.
[0043] S2. Coating resin: Clean the surface of the PF aerogel using a vapor deposition process. Mix the thermoplastic PF resin (Novolac type) with ethanol and deliver it via Ar atomization with a total carrier gas flow of 25 sccm. Control the deposition rate at 0.1-1 μm / h and hold for 1-5 seconds. After deposition, a composite material with PF aerogel inside and thermosetting PF resin (Novolac type) coating on the outside is obtained.
[0044] S3. Drying and curing: The deposited composite material is cured by gradient heating. The steps of the gradient curing are: a. Pre-curing: Raise the curing temperature to 80°C and keep it warm for 60 minutes.
[0045] b. Initial curing: Raise the curing temperature (from 80°C) to 120°C and keep warm for 120 minutes.
[0046] c. Deep curing: Then increase the curing temperature in the vacuum drying oven (from 120°C) to 150°C and keep it at this temperature for 60 minutes to complete the crosslinking.
[0047] d. Post-curing: Finally, the composite material is cooled to room temperature in the furnace, and then the material is removed by vacuum degassing.
[0048] S4. Inert atmosphere co-carbonization treatment: The composite material obtained in step (1) is placed in a graphite boat, which is then placed in a carbonization furnace. High-purity argon gas with a flow rate of 0.5 L / min is used as a protective gas. The temperature is raised from room temperature to 300°C at a rate of 5°C / min, and then raised from 300°C to 1050°C at a rate of 8°C / min. The temperature is kept at this temperature for 3 hours, and then the temperature is lowered to room temperature at a rate of 8°C / min, thereby obtaining an amorphous carbon-coated carbon aerogel composite material.
[0049] Preparation of control group 4: PF aerogel was directly carbonized according to step S4 to obtain carbon aerogel.
[0050] The linear shrinkage of the carbon aerogels of the coated sample (Example 3) and the uncoated sample (Control Group 4) is shown in Table 3. Table 3 Comparison of linear shrinkage of carbon aerogels coated with resin and those without resin
[0051] According to Table 3, compared with the control group 4, after coating the sample in the manner described in Example 3, the inert atmosphere co-carbonization treatment in step S4 can significantly reduce the linear shrinkage of the carbon aerogel composite material produced after carbonization. Example 4
[0052] This embodiment provides a method for preparing a carbonized aerogel with low shrinkage, comprising the following steps: S1. Raw material selection: A raw material combination consisting of a phenolic resin and a phenolic aerogel of the same composition is selected for use, wherein the phenolic resin selected is a modified RF aerogel, and the phenolic aerogel is a low-viscosity phenolic resin sol. The modified RF aerogel is modified by immersing the RF aerogel in an ethanol solution of a silane coupling agent, and then washing and drying with ethanol after the reaction. The low-viscosity phenolic resin sol is prepared by heating phenol to a molten state, adding a formaldehyde solution, and then dripping a low-concentration sodium hydroxide solution to adjust the pH to 8-10. The reaction is stirred at 60°C for 0.5 hours to obtain a viscosity of the low-viscosity phenolic resin sol of <50mPa·s to ensure penetration.
[0053] S2. Resin coating: Immerse the modified RF aerogel in a low-viscosity phenolic resin sol in a 50°C water bath. Use vacuum infiltration to ensure that the sol penetrates the pores of the aerogel. Remove the sample and allow the gel to stand, thereby obtaining a composite material with a modified RF aerogel inside and a low-viscosity phenolic resin sol coating on the outside. The thickness of the sprayed RF resin is controlled within 50 μm.
[0054] S3. Drying and curing: The composite material obtained in step S2 is placed in a vacuum drying oven for drying and curing. Drying and curing is performed by gradient curing of the composite material using a gradient temperature increase method. The steps of the gradient curing are: a. Pre-curing: Raise the curing temperature in the vacuum drying oven to 50°C and keep it warm for 60 minutes.
[0055] b. Preliminary curing: Raise the curing temperature in the vacuum drying oven (from 50°C) to 70°C and keep it warm for 60 minutes.
[0056] c. Deep curing: Then increase the curing temperature in the vacuum drying oven (from 70°C) to 90°C and keep it at this temperature for 120 minutes.
[0057] d. Heating and curing: Then continue to increase the curing temperature in the vacuum drying oven (from 90°C) to 120°C, and keep it warm for 240 minutes.
[0058] e. Post-curing: Finally, the composite material is cooled to room temperature in the furnace.
[0059] S4. Inert atmosphere co-carbonization treatment: The composite material obtained in step e was placed in a graphite boat, placed in a carbonization furnace, and high-purity argon with a flow rate of 0.5 L / min was used as a protective gas. The temperature was raised from room temperature to 300°C at a rate of 5°C / min, and then from 300°C to 1050°C at a rate of 8°C / min. The temperature was kept for 3 hours, and then cooled to room temperature at a rate of 8°C / min, thereby obtaining an amorphous carbon-coated carbon aerogel composite material.
[0060] Preparation of control group 5: The RF aerogel was directly carbonized according to step S4 to obtain carbon aerogel.
[0061] The linear shrinkage of the carbon aerogel composite material coated with resin (Example 4) and uncoated with resin (Control Group 5) is shown in Table 1.
[0062] Table 4 Comparison of linear shrinkage of carbon aerogels coated with resin and those not coated with resin
[0063] According to Table 4, compared with the control group 5, after coating the sample in the manner described in Example 4, the inert atmosphere co-carbonization treatment in step S4 can significantly reduce the linear shrinkage of the carbon aerogel composite material produced after carbonization. Comprehensive analysis
[0064] The linear shrinkage of the carbon aerogels prepared in Examples 1-4 and the linear shrinkage of the carbon aerogels prepared in Control Groups 1-5 (Tables 1-4) are comprehensively analyzed and the results are as follows: 1. The shrinkage inhibition effect of coating resin
[0065] A comprehensive comparison of the linear shrinkage of the carbon aerogels in Examples 1-4 and Control Groups 1-5 (excluding Control Group 3) is shown in Table 5.
[0066] Table 5
[0067] According to the data comparison in Table 5, resin coating can significantly reduce the linear shrinkage of carbon aerogel (an average reduction of 47.5%). Example 4 achieves the best inhibition effect (a reduction of 59%) through the combination strategy of vacuum infiltration and modified aerogel. 2. The key role of gradient curing process
[0068] A comprehensive comparison of the linear shrinkage of the carbon aerogels in Example 2 and Control Group 3 is shown in Table 6.
[0069] Table 6
[0070] The data in Table 6 show that, compared with constant-temperature curing, gradient curing, through a staged temperature increase (50°C → 80°C → 120°C), reduced the linear shrinkage of the carbon aerogel by 18.8%. During the gradient curing process, the pre-curing stage (50°C) eliminates residual solvent stress; the initial curing stage (80°C) establishes the primary cross-linking network; and the deep curing stage (120°C) completes the three-dimensional cross-linking structure. This demonstrates that gradient curing can avoid internal stress concentration caused by sudden temperature changes. 3. Synergistic effect of material system and process
[0071] A comprehensive comparison of the synergistic effects of the material systems and processes in Examples 1-4 is shown in Table 7.
[0072] Table 7
[0073] Table 7 shows that the optimal process is that of Example 4. In Example 4, the vacuum infiltration process forces the resin to penetrate the aerogel pores, forming a three-dimensional interpenetrating network. This provides better structural support than surface coating (spraying / brushing). Silane coupling agent modification enhances the resin-aerogel interface and inhibits interfacial slip during carbonization. A low-viscosity sol system (viscosity <50 mPa·s) ensures sufficient penetration.
[0074] In summary, the solution of Example 4 of the present application is the optimal process.
[0075] Other aspects of the present invention that are not described in detail are all conventional techniques known to those skilled in the art.
[0076] It should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or elements that are inherent to such process, method, article, or apparatus.
[0077] The protection scope of the present invention is not limited to the technical solutions disclosed in the specific implementation methods. Any modifications, equivalent replacements, improvements, etc. made to the above embodiments based on the technical essence of the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing low shrinkage carbonized aerogel, characterized in that: The following steps are involved: A raw material combination consisting of aerogel and resin of the same composition is selected; the resin in the raw material combination is evenly coated on the surface of the aerogel to obtain a composite material; the composite material is then dried and solidified; and then carbonized under inert gas to form an amorphous carbon-coated carbon aerogel.
2. The method for preparing low shrinkage carbonized aerogel according to claim 1, characterized in that: The raw material combination is any one of a combination of phenolic aerogel and phenolic resin, polyimide aerogel and polyimide resin, polyurethane aerogel and polyurethane resin, cellulose aerogel and cellulose-based resin, and epoxy aerogel and epoxy resin.
3. The method for preparing low shrinkage carbonized aerogel according to claim 1, characterized in that: The composite material is obtained by coating the resin on the surface of the aerogel in any one of sol-gel, brush coating, spray coating, spin coating, vapor deposition and solution impregnation.
4. The method for preparing low-shrinkage carbonized aerogel according to claim 3, characterized in that: The thickness of the outer resin of the composite material on one side is controlled to be ≤50 μm.
5. The method for preparing low shrinkage carbonized aerogel according to claim 1, characterized in that: The inert gas used for carbonization under inert gas is argon or nitrogen.
6. The method for preparing low shrinkage carbonized aerogel according to claim 5, characterized in that: The control parameters of the carbonization process under inert gas are: carbonization temperature of 600-1500° C., carbonization time of 1-5 hours, and heating rate to the carbonization temperature of 2-10° C. / min.
7. The method for preparing low shrinkage carbonized aerogel according to claim 6, characterized in that: The flow rate of the inert gas is 0.3-0.7 L / min.
8. The method for preparing low shrinkage carbonized aerogel according to claim 1, wherein: The drying and curing of the composite material is achieved by adopting a gradient temperature increase method.
9. The method for preparing low shrinkage carbonized aerogel according to claim 8, characterized in that: The steps of gradient curing are: a. Pre-curing: After the curing temperature is raised to 50-80℃, keep it warm for 20-40 minutes, and the heating rate is ≤5℃ / min; b. Initial curing: After the curing temperature is raised to 80℃-120℃, keep warm for 30-60min at a heating rate of 3-5℃ / min; c. Deep curing: After the curing temperature rises to 120-160℃, the holding time is 60-120min, and the heating rate is 2-3℃ / min; d. Post-curing: Cool with the furnace or control the cooling rate to ≤5℃ / min.